'Dhlakama É Maningue Nice!': An Atypical Former Guerrilla in the Mozambican Electoral Campaign - Cahen, M. (Transformation, 1998)
Despite significant problems with urban criminal gangs and highway robbers, Mozambique is a country at peace since 4 October, 1992. Under the auspices of the Italian religious congregation of Santo Egidio,4 Joaquim Alberto Chissano, president of the Republic and of the Frente de libertagao de Mozambique (FRELIMO), once the 'Marxist-Leninist' single-party of the country, and Afonso Dhlakama, president of the Resistencia national de Mogambique (RENAMO), the former guerrilla group and longtime recipient of aid from South Africa, signed the 'General Peace Accord' on that date. This agreement has never seriously been called into question. During the first 15 days following the accord there were a number of incidents. For example, it contained provisions for maintaining each party's administration in their part of the country, but did not specify the zones belonging to one party or the other. As a result, a number of RENAMO regional commanders sought to occupy areas that they had not previously controlled, the largest one being Angoche in Zambezia. It appears that they had told Afonso Dhlakama that they already held these areas, and following the peace accords, they urgently sought to gain real possession of the territory in question.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict / conflito; ⛔ No DOI found

Gender and Small Business Success: An Inquiry into Women's Relative Disadvantage - Loscocco, Karyn A.; Robinson, Joyce; Hall, Richard H.; Allen, John K. (Social Forces, 1991)
Even among a successful group of small business owners, women generate lower sales volumes and derive less income than their male counterparts. Alternative explanations of women's relative disadvantage are evaluated systematically. The characteristics of the owner and the small business that differ between genders explain the discrepancy in financial success, with the smaller size of women's businesses emerging as the major explanatory factor. Women's lack of experience and their concentration in the least profitable industries contribute strongly to the gender discrepancy as well. The processes through which the female small business owner generates sales and derives income are quite similar to those of her male counterpart, but even successful women are not as well positioned to exploit business opportunities as their male counterparts because of their structural disadvantages both within and outside of the business arena.
Number: 1 Publisher: Oxford University Press
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA

Women in Mozambique: Gender Struggle and Gender Politics - Arnfred, Signe (Review of African Political Economy, 1988)
The liberation of women is a fundamental necessity for the revolution, a guarantee of its continuity and a condition for its success (Machel, 1973). In his opening address to the first conference of the Mozambique Women's Organisation (OMM) in 1973, Samora Machel, President of Frelimo, affirmed that women's emancipation was an integral aspect of revolutionary struggle. In 1973 Frelimo was still a liberation front engaged in armed struggle against colonial rule. The northern part of Mozambique was a battle ground and the first OMM conference had to be held in the Frelimo camp at Tunduru in southern Tanzania. In the OMM's present national. secretariat in Maputo, a photograph of the participants of this first conference can be seen. Peasant women and women guerilla's are lined up outside the meeting hut, amongst them Samora Machel in battledress. The non-hierarchical atmosphere depicted in this photograph is in marked contrast to the more formal arrangements on similar later occasions. The participation of women in the war was massive. In 1967, at the request of women themselves, a women's detachment of the guerilla army - Destacamento Feminino - had been formed. Part of its task was to inform and mobilise the peasant population. To support this work, a broader non-military organisation of women was needed. This was the origin of the foundation of the OMM in 1973.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; gender / género

Ethnicity, Politics, and History in Mozambique - Alpers, Edward A. (Indiana University Press, 1974)
Conclusion Of course, the political disgrace of Joana Simiao does not by itself solve the problem of Makua-Lomwe separatism, any more than the collapse of the Movement for a Free Mozambique has solved the larger problems of national reconstruction in Mozambique. But by now it should be clear to all that the only political movement qualified to achieve that goal is FRELIMO, who demonstrably are working for the interests of all Mozambicans and who enjoy the support of Mozambicans of all races, religions, and ethnic backgrounds, including both Makua-Lomwe and Maconde. During its decade of armed struggle FRELIMO has successfully defended its just cause against attack from without and dissension from within. In the process it has painstakingly built a truly national liberation movement. The lessons learned in that crucible, which se suddenly belongs to the past, must now be applied to the future
Publisher: Indiana University Press
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; politics / política; ⛔ No DOI found